Do government subsidies promote green R&D efficiency? Empirical evidence from China - WU, Huimin (Institutional Knowledge at Singapore Management University, 2023)
How to evaluate the effects of government policy on encouraging innovations? Existing studies strongly argue to reduce subsidies compared to indirect policy tools, such as tax rebate. However, direct government grants are popular and keep gaining momentum in China. Such a discrepancy between academic research and common practice is interesting and calls for further investigations. In the meantime, is there any difference for this issue if considering green attributes? In this article, we use data from Chinese A-share listed companies to study the effect of government subsidies on R&D activities, with a special focus on comparing green and non-green inventions. Our result shows that green attributes of innovation bring in heterogeneity in R&D intentions, market competition effects, and government subsidy incentives. Specifically, first, companies are less willing to pursue green innovations due to positive environmental externalities. Second, while market competition substantially stimulates non-green innovations, it does not have a positive effect on the efficiency of green R&D activity, or, even worse, inhibits it. Third, government subsidies are more effective in spurring green R&Ds, compared to non-green ones. A closer look at the above results demonstrates that official green performance evaluation in China may play an important role. Green innovations are subject to more monitoring efforts by the government, which dissuades R&D manipulation by firms. Our study emphasizes the necessity of government policies as well as their combination with market competition. Specifically, we recommend the adoption of generous and comprehensive subsidy policy with rigorous supervision for green ones. We strongly suggest future research consider the possible heterogeneity of green attributes in R&D to avoid omitted variable bias.